2020
DOI: 10.1038/s41598-020-79605-3
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole impairs fracture healing in aged mice

Abstract: Proton pump inhibitors (PPIs) belong to the most common medication in geriatric medicine. They are known to reduce osteoclast activity and to delay fracture healing in young adult mice. Because differentiation and proliferation in fracture healing as well as pharmacologic actions of drugs markedly differ in the elderly compared to the young, we herein studied the effect of the PPI pantoprazole on bone healing in aged mice using a murine fracture model. Bone healing was analyzed by biomechanical, histomorphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
1
9
2
Order By: Relevance
“…Of interest, we failed to observe a significant difference of serum calcium level and amount of daily calcium intake among non-user, PPI user, and H2RA user, but our result still showed an association of PPI use with lower BMD. A recent study demonstrated that pantoprazole accelerated bone turnover by affecting the number of osteoclasts and decreased the expression of bone morphogenetic protein-4 (BMP-4) in aged mice, indicating PPIs may affect bone metabolism by regulating bone formation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, we failed to observe a significant difference of serum calcium level and amount of daily calcium intake among non-user, PPI user, and H2RA user, but our result still showed an association of PPI use with lower BMD. A recent study demonstrated that pantoprazole accelerated bone turnover by affecting the number of osteoclasts and decreased the expression of bone morphogenetic protein-4 (BMP-4) in aged mice, indicating PPIs may affect bone metabolism by regulating bone formation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CD-1 outbred mouse has been used in a variety of experimental studies to investigate the effects of pharmacological substances on fracture healing [7][8][9] and develop novel treatment strategies to facilitate bone regeneration [10,11]. Additionally, CD-1 mice have been successfully applied in orthopedic research, which focuses on fracture healing in aged animals [12,13]. However, to our knowledge, no study has yet compared the radiographic, biomechanical and histological healing properties of aged animals with those of young adult CD-1 mice.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, the intrinsic angiogenic response was sufficient for adequate vascularization during non-union formation, however, the failure of fracture healing was associated with a decreased expression of the pro-osteogenic proteins BMP-2 and BMP-4 [ 79 ]. Moreover, our own recent investigation on the effects of pantoprazole on fracture healing in aged mice demonstrated that impaired bone healing is associated with a decrease in the protein expression ratio of pro-osteogenic to pro-angiogenic growth factors, such as VEGF and cysteine rich protein(CYR)61 [ 80 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%